Prevalence and sociodemographic predictors of high-risk vaginal human papillomavirus infection: findings from a public cervical cancer screening registry - Anis-Syakira Jailani; Nur Zahirah Balqis-Ali; Kar Foong Tang; Weng Hong Fun; Shazimah Abdul Samad; Rohaidza Jahaya; Nurun Najihah Subakir; Roziah Ismail; Zakiah Mohd Said; Sondi Sararaks (BMC, 2023)
Abstract Introduction High-risk human papillomavirus (HPV) screening is vital for early cervical cancer detection and treatment. With the introduction of the national cervical cancer screening programme and screening registry in Malaysia, there is a need to monitor population-based HPV screening uptake and high-risk HPV prevalence as part of cervical cancer surveillance. Objective To determine the prevalence and sociodemographic factors predicting high-risk HPV infection in Malaysia based on a public, community-based cervical cancer screening registry targeting women at risk of getting HPV infection. Methods The study used data from the Malaysian cervical cancer screening registry established by the Family Health Development Division from 2019 to 2021. The registry recorded sociodemographic data, HPV test details and results of eligible women who underwent HPV screening at public primary healthcare facilities. A vaginal sample (via self-sampling or assisted by a healthcare provider) was used for DNA extraction for HPV detection and genotyping. Registry data were extracted and analysed to determine prevalence estimates of high-risk HPV infection. Multifactorial logistic regression analysis was conducted to determine predictors of high-risk HPV infection. All analyses were performed using Stata version 14. Results The programme screened a total of 36,738 women during the study period. Women who attended the screening programme were mainly from urban areas, aged 30-39 years, and of Malay ethnicity. The prevalence of high-risk HPV infection was 4.53% among women screened, with the yearly prevalence ranging from 4.27 to 4.80%. A higher prevalence was observed among urban settling women, those aged 30-49 years, those of Indian ethnicity, and those without children. The results from logistic regression showed that women from urban areas, lower age groups, of Indian or Chinese ethnicity, and who are self-employed were more likely to be infected with high-risk HPV. Conclusion Targeted and robust strategies to reach identified high-risk groups are needed in Malaysia. In addition, the registry has the potential to be expanded for an improved cervical cancer elimination plan. Trial registration Trial registration number: NMRR ID-22-00187-DJU.